Leidy Munera!
·
Aquí hay que usar unas identidades que habrás dado en la teoría:
$$\begin{align}&sen(a+b) = sena·cosb+cosa·senb\\&sen(a-b) = sena·cosb-cosa·senb\\&\cos(a+b) = cosa·cosb - sena·senb\\&\cos(a-b) = cosa·cosb + sena·senb\\&\\&\text{con lo cual}\\&\\&sen(a+b)+sen(a-b)=\\&sena·cosb+cosa·senb+sena·cosb-cosa·senb=\\&2·sena·cosb\\&\\&\\&\\&\cos(a+b)-\cos(a-b)=\\&cosa·cosb - sena·senb - (cosa·cosb + sena·senb)=\\&cosa·cosb - sena·senb - cosa·cosb - sena·senb)=\\&-2sena·senb\\&\\&\\&\\&sen(a+b)-sen(a-b) =\\&sena·cosb+cosa·senb-(sena·cosb-cosa·senb)=\\&sena·cosb+cosa·senb-sena·cosb+cosa·senb=\\&2cosa·senb\\&\end{align}$$
·
Y eso es todo.